Knowledge, Attitude and Practices of Health Workers regarding Medical Waste Management in Entebbe Regional Referral Hospital, Wakiso District. A Cross-sectional Study. - Hanisha Lwasa Nakawooma; Gordon Nimwesiga (Student's Journal of Health Research Africa, 2022)
Background: